Educational planning - Franco, Ernesto A. (Metro Manila, Philippines : National Book Store, 1994)
There will be many occasions where some topics or subject matters appears to be repeated, or represented twice but always with some significant variation crucial to a better understanding of the issue concerned and also to examine the problem from another angle or perspective.
Part 1. Concepts: Planning, Plan for Planning, Planning Process and Replanning. -- Part 2. Implementation, Approaches, Models and Guidelines for Planning. -- Part 3. Planning at the institutional Level.
Keywords: EDUCATIONAL PLANNING -- PHILIPPINES